Factores asociados a mala calidad de sueño en pacientes con insuficiencia renal crónica en hemodiálisis - Peña Martínez, Bruce (2015)
Introduction and objectives Sleep disorders are one of the most common comorbidities among patients on hemodialysis. The aims of this study were to determine the prevalence of poor sleep quality as well as to establish potential factors associated with poor sleep quality. Materials and methods A cross-sectional study was performed enrolling patients with chronic kidney disease on hemodialysis. The outcome was sleep quality evaluated using the Pittsburgh Scale, whereas the exposure variables were time on hemodialysis, history of type-2 diabetes and hypertension, depressive symptoms, anemia, and uremia. We used Poisson regression model to determine the association of interest, reporting prevalence ratios (PR) and 95% confidence intervals (95%CI). Results A total of 450 patients were enrolled, 259 (57.5%) were male, aged from 18 to 97 years. The prevalence of poor sleep quality was 79.3% (95%CI: 75.6%–83.1%). Poor sleep quality was associated with depressive symptoms (PR = 1.28; 95%CI: 1.17-1.39), anemia (PR = 1.18; 95%CI: 1.04-1.34) and uremia (PR = 1.26; 95%CI: 1.17-1.36) after controlling for potential confounders. Conclusions The presence of depressive symptoms, anemia and uremia were positively associated with poor sleep quality among patients with chronic kidney disease on hemodialysis. A great proportion of this population had poor sleep quality. Strategies are needed to improve sleep quality in these patients.